2002
DOI: 10.1046/j.1365-2427.2002.00830.x
|View full text |Cite
|
Sign up to set email alerts
|

Gradients in stream fish assemblages across a Mediterranean landscape: contributions of environmental factors and spatial structure

Abstract: 1. Despite wide recognition that fish assemblages are influenced by factors operating over a range of spatial scales, little effort has been devoted to quantifying large‐scale variation and the multiscale dependencies of assemblage patterns and processes. This is particularly true for Mediterranean streams, where seasonally predictable drying‐up may lead to a strong association between assemblage attributes and large‐scale factors affecting the distribution of population sources and extinction likelihood. 2. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
181
3
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(213 citation statements)
references
References 40 publications
(58 reference statements)
24
181
3
2
Order By: Relevance
“…Accordingly, similar pattern in species diversity was observed. These results are in accordance with numerous previous studies (Godinho et al, 1997(Godinho et al, , 2000Carmona et al, 1999;Pires et al, 1999Pires et al, , 2004Mesquita and Coelho, 2002;Magalhães et al, 2002aMagalhães et al, , 2002bMagalhães et al, , 2007Clavero et al, 2004;Ferreira and Oliveira, 2004;Clavero and Garcia-Berthou, 2006;Mesquita et al, 2006;Ferreira et al, 2007aFerreira et al, , 2007b. In fact, increasing local species richness along the longitudinal stream gradient is a very well known pattern (e.g.…”
Section: Figuresupporting
confidence: 93%
See 1 more Smart Citation
“…Accordingly, similar pattern in species diversity was observed. These results are in accordance with numerous previous studies (Godinho et al, 1997(Godinho et al, , 2000Carmona et al, 1999;Pires et al, 1999Pires et al, , 2004Mesquita and Coelho, 2002;Magalhães et al, 2002aMagalhães et al, , 2002bMagalhães et al, , 2007Clavero et al, 2004;Ferreira and Oliveira, 2004;Clavero and Garcia-Berthou, 2006;Mesquita et al, 2006;Ferreira et al, 2007aFerreira et al, , 2007b. In fact, increasing local species richness along the longitudinal stream gradient is a very well known pattern (e.g.…”
Section: Figuresupporting
confidence: 93%
“…communities sampled at a small spatial extent) are structured by a combination of historic, regional, and local factors operating at different spatial and temporal scales (Poff, 1997;Whittaker et al, 2001;Hoeinghaus et al 2007). Whether are large-scale (Schlosser, 1991;Marsh-Matthews and Matthews, 2000;Magalhães et al, 2002a;Hoeinghaus et al, 2007) or local environmental factors (Ricklefs and Schluter, 1993;Ricklefs, 2006), the principal determinants of community structure continuous to be a widely debated issue. At larger spatial scales, historic (e.g.…”
Section: Figurementioning
confidence: 99%
“…Differences between precipitation and river flow in autumn 2007, spring 2008 and autumn 2009 were evident, which seems related with dam operations. The marked seasonal and inter-annual variability of precipitation regime are key factors structuring freshwater fish assemblages in Mediterranean streams (Magalha˜es et al, 2002) which is also evident in Minho TFWs (this work). For example, higher water temperatures had a significant negative effect on the observed number of species, but a positive effect on the abundance and biomass of NIS.…”
Section: Abiotic Characterizationsupporting
confidence: 55%
“…Poff, 1997;Porter et al, 2000;Higgins and Strauss, 2008). Some of these studies indicated that fish assemblages can be structured not only by local processes, but also by large-scale environmental factors (Magalha˜es et al, 2002;Hoeinghaus et al, 2006). Thus, to understand the fish species-habitat relationships multiscale approaches are necessary (Ferreira et al, 2007).…”
Section: Introductionmentioning
confidence: 99%